Особливості проектування житлових будинків у забудові історичного центру міста - Рогожникова, Олена Євгенівна; Халімон, М. М.; Rogozhnykova, O. E.; Khalimon, M. M. (КНУБА, 2019)
Проаналізовано містобудівні аспекти функціонування історичної забудови в центральних районах міста в умовах розвитку будівництва і безперервного підвищення конструктивних, економічних, санітарних вимог до будівель. The urban aspects of the function of historic buildings in the central parts of the city under construction development conditions and non-stop raising engineering, economic, and health requirements for buildings has been analysed. The article considers optimal space planning solutions for the residential complexes. The practical need for effective architecture planning tools in the future has been grounded.
The peculiarities of residential houses design in the historic centre development of the city
Keywords: історична забудова; пам’ятки архітектури; реконструкція; архітектурне середовище; historical building; architectural environment; reconstruction; landmark